2018
DOI: 10.1097/rhu.0000000000000612
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Antidrug Antibodies in Rheumatoid Arthritis Patients From Argentina Treated With Adalimumab, Etanercept, or Infliximab in a Real-World Setting

Abstract: In this subset analysis, RA patients from Argentina treated with adalimumab or infliximab, but not etanercept, tested positive for ADAs. Antidrug antibody-negative patients showed a tendency toward better clinical outcomes compared with ADA-positive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Concerns have been raised over the therapeutic implications of the development of neutralizing antidrug antibodies to bDMARDs [15,16], which may be the underlying rationale for recommending continuation with methotrexate monotherapy once good disease control has been achieved on combination therapy. The development of neutralizing antidrug antibodies to TNFis other than etanercept have been reported [15,16,[30][31][32][33][34], and may be one factor contributing to the different persistence rates detected in our study. Similarly, the higher discontinuation rates reported for other TNFis than for etanercept in long-term registry studies [35,36] is consistent with our findings.…”
Section: Discussionmentioning
confidence: 63%
“…Concerns have been raised over the therapeutic implications of the development of neutralizing antidrug antibodies to bDMARDs [15,16], which may be the underlying rationale for recommending continuation with methotrexate monotherapy once good disease control has been achieved on combination therapy. The development of neutralizing antidrug antibodies to TNFis other than etanercept have been reported [15,16,[30][31][32][33][34], and may be one factor contributing to the different persistence rates detected in our study. Similarly, the higher discontinuation rates reported for other TNFis than for etanercept in long-term registry studies [35,36] is consistent with our findings.…”
Section: Discussionmentioning
confidence: 63%
“…There are several clinical studies comparing treatment efficacy and side-effects between infliximab, adalimumab, and etanercept [239][240][241][242]. Here, it was shown that TNF-α neutralizing antibodies possess a high potential to induce the production of anti-drug antibodies (ADAs) (detection of ADAs within 18 months of treatment in either the adalimumab (19.2%-31.2% of patients) or infliximab group (17.4-29.4% of patients)) [239][240][241]243]. ADAs can not only decrease drug levels in serum, but also raise safety concerns like induction of type I-III hypersensitivity responses [244].…”
Section: Tnf-α Inhibitorsmentioning
confidence: 99%
“…The lack of the human Fc domain in certolizumab pegol reduces the possibility for ADA generation. Consequently, clinical results demonstrated that none or only low levels of ADAs were detected in certolizumab pegol-treated patients [241], while several studies indicated a high immunogenicity of both infliximab and adalimumab which might lead to the development of ADAs [239][240][241]243]. The induction of ADAs against adalimumab and infliximab is associated with both major and minor clinical adverse effects [243].…”
Section: Tnf-α Inhibitorsmentioning
confidence: 99%
“…For example, the presence of IL‐6 and IL‐1 β in parallel with TNF‐α may lead to inhibition of erythropoiesis, which, unlike the myeloid lineage, leads to a decrease in erythrocyte counts (Pierce & Larson, 2005). Inhibition of TNF‐α using TNF‐α signaling inhibitors such as infliximab, etanercept, adalimumab, and golimumab could be an effective approach to reverse erythropoiesis and increase erythroid precursors in BM diseases as well as preventing inflammation in inflammatory diseases (Table 2; Brenner et al, 2015; Maid et al, 2018). Thus, although the presence of TNF‐α may play a role in stimulating hematopoiesis (induction of megakaryopoiesis and myeloid differentiation), TNF‐α inhibition could also lead to the recovery of erythropoiesis and prevent the progression of inflammation.…”
Section: Tumor Necrosis Factor‐αmentioning
confidence: 99%